The geographical distribution of the malaria vector Anopheles arabiensis in Cabo Verde, 2016–2023 - Silvânia Da Veiga Leal; Celivianne de Sousa; Davidson Daniel Sousa Rocha Monteiro; Maria da Luz Lima Mendonça; Adéritow Augusto Lopes Macedo Gonçalves; Adilson José DePina (Frontiers in Tropical Diseases, 2024)
BackgroundIntegrated malaria vector control is crucial to eliminate or reduce infection risk. Understanding vector species distribution, behavior, and environmental factors such as climate, topography, and preferred aquatic habitats is essential.ObjectivesHerein, we aim to compile data from 2016 to 2023 on the primary malaria vector in Cabo Verde to support health surveillance and elimination certification.Materials and methodsMosquitoes larvae were collected using standard sampling tools, and adults using Biogents Sentinel traps, mechanical aspiration and CDC UV light traps, both indoor and in the surroundings of urban and rural areas.ResultsSix hundred fifty-seven specimens of Anopheles gambiae s.l. were identified by morphological methods and PCR-based techniques as Anopheles arabiensis in 12 municipalities from six of the nine inhabited islands, namely, São Vicente, São Nicolau, Maio, Boavista, Santiago, and Santo Antão.ConclusionsWe believe this is the first scientific report of the presence of An. arabiensis on the island of Santo Antão. The Anopheles arabiensis remains the only species in the An. gambiae complex in the Cabo Verde islands. These results offer vital insights for epidemiological surveillance and effective malaria control, especially in light of the recent WHO certification declaring the country malaria-free. However, it is imperative to conduct further studies that comprehensively address epidemiological and entomological aspects, with a special focus on bionomics, genetic determinants of the parasite-vector association, and the characterization of larval habitats. These investigations have the potential to guide a more informed and strategic implementation of malaria vector control measures in Cabo Verde.